Assisted velocity swimming training in two and six beats age group front crawl swimmers - Pretto, L.; Castro, F.; de Oliveira, A. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study was to verify the effects of an assisted velocity training (AVT) on stroke rate (SR) and time to perform 25 m in front crawl stroke with 2 and 6 beats kicks in age group front crawl swimmers. Ten swimmers (13 to 15 years old) allocated in group 2 beats (TB; n = 5) and group 6 beats (SB; n = 5) performed, before and after 6 weeks of training, a 25 m maximal effort in front crawl. First 5 stroke cycles, after 10m, were recorded manually, to obtain SR and time to perform the 25 m. AVT was applied twice a week. It consisted of 8 trials of 20 m (1 min rest). A 7 m length and 203 mm thickness rubber band was fixed to the pool edge and to a belt around the swimmer's waist. Subjects were towed by the coach into the 20 m to perform back in high assisted velocity. Results showed increased values just on SR for TB after the AVT. This increase in SR values has not affected the time to perform the 25 m.